If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -113 = -2x + -3(-1x + 35) Reorder the terms: -113 = -2x + -3(35 + -1x) -113 = -2x + (35 * -3 + -1x * -3) -113 = -2x + (-105 + 3x) Reorder the terms: -113 = -105 + -2x + 3x Combine like terms: -2x + 3x = 1x -113 = -105 + 1x Solving -113 = -105 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -113 + -1x = -105 + 1x + -1x Combine like terms: 1x + -1x = 0 -113 + -1x = -105 + 0 -113 + -1x = -105 Add '113' to each side of the equation. -113 + 113 + -1x = -105 + 113 Combine like terms: -113 + 113 = 0 0 + -1x = -105 + 113 -1x = -105 + 113 Combine like terms: -105 + 113 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 3x-4=8x+16 | | 3m+v=-0.11+5v | | 2+1+f=-f+7f-2 | | 83=19+y | | -56x^2y^3/16x^4y^-1 | | 3x+14=98 | | 10(8)(x)=120 | | 48=-28+f | | -5(7-5)-8= | | s=3t^3-2t | | 1/4*1/9 | | -4(1-5b)=-124 | | -5(-5-7)+9= | | 0.5(x-1)=0.33(x+1) | | 20*-0.4= | | 2b/2+b/4-4/2=34/8 | | 2y^2=7y | | 2(9+5)-8= | | 62=-6x-2(-x-9) | | 4-20(-0.4)= | | 0=-16x^2+12-4x+3 | | 3*(1+n)=9+n | | -4y-2=9y-3 | | 7=3+6 | | 4-20(-8)= | | 0.20x+6=14 | | 10=25-5T-T^2 | | 6a-5=-3a | | 7/2x-3x=-1/2x+3/2+5/2x | | 0=-16t^2+240t | | 7m=9m+36 | | 20*-8= |